Determinants of Behavior-Based Safety Performance in Coal-Fired Power Plants Using Structural Equation Modeling - Aulia Maulana Azkiya; Prima Vitasari; Renny Septiari (Universitas Panca Marga, 2026)
Occupational safety is a critical issue in coal-fired power generation industries due to the high-risk nature of operational and maintenance activities. Preliminary observations at a power generation company identified several unsafe behaviors, including non-compliance with work permits, improper use of personal protective equipment (PPE), violations of standard operating procedures, unsafe workplace arrangements, and inappropriate behavior during hazardous activities. This study aimed to identify factors influencing Behavior-Based Safety (BBS) and determine the most significant predictors of employees’ safety behavior. A quantitative cross-sectional approach was applied, with data analyzed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). The results indicated that employee attitude (p = 0.004) and the implementation of occupational health and safety (OHS) regulations (p = 0.003) had significant positive effects on safety behavior (p < 0.05). Meanwhile, safety knowledge, work motivation, PPE availability, OHS training, reward systems, and punishment mechanisms showed no significant influence on BBS (p > 0.05). These findings highlight that strengthening safety attitudes and organizational OHS implementation plays a more dominant role in improving employee safety behavior compared to knowledge-based and incentive-based interventions. The SEM model developed in this study can support safety management strategies and contribute to establishing a sustainable zero-accident culture in high-risk industries.